The Effects of Organizational Context on Quality Management: An Empirical Investigation - Benson, P. George; Saraph, Jayant V.; Schroeder, Roger G. (Management Science, 1991)
While the quality literature abounds with prescriptions for how quality should be managed, no one has proposed an organization-theory explanation for how quality is managed in organizations. This paper proposes a system-structural model of quality management that relates organizational quality context, actual quality management, ideal quality management, and quality performance. The relationships between organizational quality context and actual and ideal quality management are investigated using data collected from 152 managers from 77 business units of 20 manufacturing and service companies. A previously reported instrument is used to measure managers' perceptions of ideal and actual quality management in terms of eight critical factors including product/service design, training, employee relations, and top management leadership. Several measures are used to characterize organizational quality context including company type, company size, degree of competition, and corporate support for quality. The results indicate that organizational quality context influences managers' perceptions of both ideal and actual quality management. This suggests that knowledge of organizational quality context is useful for explaining and predicting quality management practice. Important contextual variables are corporate support for quality, past quality performance, managerial knowledge, and the extent of external quality demands.